حقوق الأقليات في الدساتير العراقية ما بعد عام 2003 - الجبوري، عمر فرحان حمد (جامعة الكتاب, 2018)
يعد قانون إدارة الدولة العراقي لسنة 2003 والدستور العراقي لسنة 2005، نقطة تحول في تاريخ الأقليات في العراق، حيث نص على حقوق لم تتطرق لها الدساتير العراقية منذ نشأة الدولة العراقية وحتى عام 2003، إذ نص على الحقوق السياسية والثقافية كافة وغيرها من الحقوق وحتى الحقوق المتعلقة باستخدام اللغة لتلك الأقليات، وأهم شيء فإنه قد نص عليه الدستور العراقي هو استخدام مفردة وصفه مكونات بدلا من أقليات، لكن هذه الأخيرة مازالت تحمل معاناة سياسية من خلال عدم وجود تشريعات تحقق ما ثبته الدستور، إذ بقيت أغلب هذه الحقوق المنصوص عليها في الدساتير حبرا على ورق، فالسبب يكمن في آلية التطبيق وليس في آلية النص على الحقوق ولذلك برزت العديد من الإشكاليات أهمها إشكالية الهوية الوطنية العراقية. The Iraqi State Administration Act of 2003 and the Iraqi Constitution of 2005 are a turning point in the history of minorities in Iraq. They stipulate rights that have not been addressed by the Iraqi constitutions since the inception of the Iraqi state until 2003. They stipulated all political and cultural rights and other rights, Using the language of these minorities, and the most important thing that was stipulated by the Iraqi constitution is the use of a single description of components rather than minorities, but the latter still bear political suffering through the absence of legislation to verify the Constitution, as most of these rights provided for in constitutions Paper, then the reason lies In the mechanism of application and not in the mechanism of the provision of rights and therefore emerged many of the most problematic issues, including the problematic national identity of Iraq.
Keywords: حماية الأقليات -- الأقلية الدينية -- حقوق الأقليات -- الهوية القومية -- القانون العراقي